Pressure fluctuations and flow-induced vibration measurements in a hard disk drive under different rotation speeds - Min, Hequn (2013)
Flow-induced vibration (FIV) of a head gimbals assembly (HGA) in hard disk drives (HDDs) limits the positioning accuracy of magnetic head in the HGA for higher HDD magnetic recording density. The pressure fluctuations characterize turbulent fluctuations exciting the HGA off-track vibration (HGA-OTV). In this paper, experimental studies have been carried out to investigate the spectrum characteristics correspondence between pressure fluctuations around an HGA and the simultaneous HGA-OTV under different HDD rotation speeds. A practical and effective experimental setup has been implemented to enable the simultaneous measurements on both the pressure fluctuation and HGA-OTV signals, where pressure fluctuations are measured with a pressure transducer through a small hole on the HDD top cover and the direct HGA-OTV signals are detected through a laser Doppler vibrometer. Results under conditions of three different HDD rotation speeds of 7200, 9000, 10800 rpm have been investigated and compared. It is shown that the HGA off-track vibration spectra are highly associated with those of the pressure fluctuations in terms of principal peaks in four frequency bands around 1.8 kHz, 2.5-3.5 kHz, 7-7.5 kHz and 11.5-12.5 kHz. With increasing HDD rotation speed, it is shown that the spectrum magnitudes of both the pressure fluctuation and the HGA off-track vibration increase correspondingly, while the principal peak positions in spectra of either pressure fluctuation or the HGA off-track vibration always hold the line. This study demonstrates a causal nexus from the pressure fluctuation to the HGA off-track vibration and suggests the feasibility of controlling the HGA-OTV through suppression of pressure fluctuations around the HGA.